2019
DOI: 10.1051/kmae/2019017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of common carp (Cyprinus carpio) on water quality in aquatic ecosystems dominated by submerged plants: a mesocosm study

Abstract: Common carp (Cyprinus carpio) have been introduced into aquatic systems across the world, where their benthivorous feeding behavior has resulted in serious water quality problems. A 12-week mesocosm experiment was set up to test the hypotheses that common carp increase water column nutrient levels and decrease water clarity in aquatic ecosystems dominated by submerged plants. Further, we tested whether the effect of common carp on macrophytes depended on the species of plants. Relative to the controls, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
1
9
1
Order By: Relevance
“…The presence of fish increased the planktonic algal biomass, TSS and ISS and decreased the light intensity. Other investigations have shown that Prussian carp can increase turbidity, decrease benthic algae biomass and enhance the release of nutrients from the sediment to the water, becoming available for and promoting planktonic algae growth [26,28]. Our results are, in part, consistent with these findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The presence of fish increased the planktonic algal biomass, TSS and ISS and decreased the light intensity. Other investigations have shown that Prussian carp can increase turbidity, decrease benthic algae biomass and enhance the release of nutrients from the sediment to the water, becoming available for and promoting planktonic algae growth [26,28]. Our results are, in part, consistent with these findings.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, omnivorous fish can predate on phytoplankton-consuming zooplankton, thereby reducing their abundance and changing their community structure [22][23][24]. They may, however, also increase turbidity through resuspension of bottom sediments when feeding [25][26][27], potentially with negative effect on primary producers. Omni-benthivorous fish may also affect the plants by uprooting or by consuming them.…”
Section: Introductionmentioning
confidence: 99%
“…In our experiment, however, concentrations of ISS were low in the BF mesocosms. This result, which indicates that bitterling did not enhance sediment resuspension, contrasts with most findings for larger benthivorous fishes, such as carp (Gu et al 2016, Zhang et al 2016, He et al 2019, Qiu et al 2019. Bitterling excretion may, therefore, be the key factor affecting nutrient levels (higher TDN and TDP) in the BF mesocosms.…”
Section: Effects Of Bitterling On Water Physicochemical Parameters Ancontrasting
confidence: 77%
“…Lakes in temperate areas are particularly prone to milfoil invasion due to the high levels of natural disturbance from freeze-thaw, drought, storms, and other sources (Capers et al, 2007). Biotic factors such as native species density (Capers et al, 2007), presence of herbivore species (Qiu et al, 2019), and propagule pressure (Levine, 2000;Lockwood et al, 2005) potentially influence invasion resistance. Myriophyllum spicatum occurs in shallow water (1-4 m), grows quickly (Smith and Barko, 1990), is a strong light competitor, and often rapidly colonizes disturbed areas (Madsen et al, 1991).…”
Section: Introductionmentioning
confidence: 99%